Development of a Lightweight Weather Forecasting Application Using Javascript (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Weather forecasting plays a vital role in various domains, including agriculture, transportation, and disaster management. This paper presents the development of a lightweight weather forecasting application using JavaScript, designed to provide real-time weather information through a web-based interface. The application leverages publicly available weather APIs for data retrieval and integrates responsive design principles to ensure usability across multiple platforms. By utilizing JavaScript’s asynchronous capabilities and client-side rendering, the system delivers an interactive and efficient user experience without requiring heavy server-side computation. The proposed solution emphasizes simplicity, portability, and accessibility, making it suitable for users with limited computational resources. Experimental evaluation demonstrates that the application achieves fast response times and reliable accuracy in displaying weather conditions, thus offering a practical and cost-effective tool for real-time weather monitoring.